PENERAPAN INARISK PERSONAL BAGI MASYARAKAT PURWODADI DI KECAMATAN ARGAMAKMUR KABUPATEN BENGKULU UTARA SEBAGAI UPAYA MITIGASI BENCANA DAN PENULARAN COVID-19 - Ferry Lismanto Syaiful; Efrizal Efrizal; Desry Fitria Marliana (LPPM Universitas Andalas, 2022)
The InaRisk Personal application is an application that displays the level of hazard/disaster hazard in an area equipped with mitigation suggestions before, during, and after a disaster to reduce disaster risk. This InaRisk application was developed by the Disaster Management Agency (BNPB), which can be obtained on Android and IOS; this is certainly beneficial for the community. The purpose of this activity is 1. to provide education on the use of the InaRisk Personal Application for the people of Purwodadi, North Bengkulu in facing the threat of disaster hazards around them and suggestions for mitigation, 2. to find out the pattern of transmission of the Covid-19 virus and the level of risk of being exposed to Covid-19 in order to support government programs to prevent the spread of Covid-19. This activity was carried out in Purwodadi Village, Argamakmur District, North Bengkulu Regency, with the target of this activity being the people of Purwodadi, Argamakmur. The method of activities carried out is socialization, implementation of the InaRisk Personal application, and evaluation of activities. From the activities that have been carried out, this activity can increase knowledge and understanding and the benefits of using the InaRisk application for the community. The application of this InaRisk application so that the public gains knowledge about the level of disaster hazard in their area to reduce the risk of the disaster. Through the InaRisk application, the people of Purwodadi, North Bengkulu, can also find out the level of risk of being exposed to Covid-19 based on their lifestyle and advice on preventing the transmission of Covid-19. Furthermore, the public is educated through the InaRisk application so that people are aware and do not ignore health protocols. On the other hand, the InaRisk application for the community is undoubtedly useful and supports the government's program, namely the prevention of Covid-19 transmission.